DNA repair gene XRCC1 polymorphisms and susceptibility to childhood acute lymphoblastic leukemia: a meta-analysis - Du, Juan; Lu, Cong; Cui, Guohui; Chen, Yan; He, Jing (Chinese Journal of Cancer Research, 2013)
Objective: To estimate the relationship between genetic polymorphisms of X-ray repair crosscomplementing group 1 (XRCC1) and the susceptibility to childhood acute lymphoblastic leukemia (ALL). Methods: Relevant case-control studies were enrolled in the meta-analysis. We applied Rev Man 4.2 software to pool raw data and test studies’ heterogeneity and to calculate the incorporated odds ratio (OR) and 95% confidence interval (95% CI). Results: Our data showed that the OR for the Gln allele of the Arg399Gln polymorphism, compared with the Arg allele, was 1.35 (95% CI, 1.16-1.57; P